Please take a look at the picture. Please write your answer with an explanation.
![Please take a look at the picture Please write your answer with an explanation class=](https://us-static.z-dn.net/files/d41/7e4474bfb97c010c6ad91fee72ecfa0b.png)
Answer:
-1
Step-by-step explanation:
We are given the expression:
-5x + 6y - 7y + 4x
With condition x = -3, y = 4
Therefore, substitute x = -3 and y = 4.
-5(-3) + 6(4) - 7(4) + 4(-3)
Recall every important fundamental math such as multiplying with negative.
15 + 24 - 28 - 12
Evaluate:
39 - 40
-1
Alternative solution is to combine like terms first before substitution.
-x - y
Thus:
-(-3) - 4
3 - 4
-1